Enhancing the Laboratory Quality Assurance using the MyKIMIA Proficiency Testing Provider (PTP) Food Scheme Data - Li Hui Ling; Mohd Sukri Hassan (Universiti Kebangsaan Malaysia, 2024)
Indexed by MyCite